Phaseolus vulgaris Linn: An Overview - M. Devi; R. Praveen; R. Sneha Sri; G. E. Thillai Govindarajan (Advanced Concepts in Pharmaceutical Research Vol. 1, 2023)
Black beans (Phaseolus vulgaris L.) are most widely consumed in China, India, and America due to their unique taste and potent health benefits attributed to their higher content of phytochemicals. Researchers have extensively explored the phenolic profile and biological properties of black beans. Since ancient times, restorative spices have been discovered and used in traditional medical practices. The French bean, or Phaseolus vulgaris Linn. (Family: Fabaceae), is a carbohydrate and protein-rich food crop with healing properties that is extremely enticing. This plant contains a variety of nutrients, including carbohydrates, proteins, flavonoids, saponins, tannins, and phenolic acids. The seeds of Phaseolus vulgaris Linn. have having Hostile to urolithiatic action and Against stoutness action. This survey gives a rundown of phytochemistry and pharmacological impact of Phaseolus vulgaris Linn., The plant can be additionally researched for other pharmacological exercises as it contains assortment of compound constituents and it is a generally utilizing food yield and clinical cures of this plant are sync with nature.